Gymnodactylus turcmenicus sp. n. (Reptilia, Sauria) —новый вид геккона из Южной Туркмении - Щербак, Н.Н. (Вестник зоологии, 1978)
A new species of gecko, Gymnodactylus turcmenicus, found in the South of Turkmenia in the outskirts of vil. Morgunovka is described. The given species is the largest among G. caspius., G. fedtschenkoi and G. longipes close to it and differs distinctly in pholidosis characters. A new key is compiled to differentiate geckoes of the Cyrtodactylus subgenus of the USSR fauna.